Prologue 2008 - Allsop, Sara; Brager, Kyle; Brigman, Austin D.; Buckvold, Marilyn; Butler, Margaret; Carlson, Christine; Fechner, Lauren; Fischer, Julie R.; Gaffer, Kathy; Germain, Maria; Haden, Margaret; Hoffman, Jesse; et al. (University of Wisconsin-River Falls, 2008)
2008 edition of Prologue, the University of Wisconsin-River Falls student literary and art publication.
iv, 68 p.
Keywords: University of Wisconsin--River Falls--Periodicals; University of Wisconsin--River Falls--Students; University of Wisconsin--River Falls--Students--Periodicals; College verse--Wisconsin--River Falls; College prose--Wisconsin--River Falls; Arts--Wisconsin--River Falls; College student newspapers and periodicals--Wisconsin--River Falls; Student publications--Wisconsin--River Falls; University of Wisconsin--River Falls; Prologue; Student literary and art publication; Literary works; Original art works; Serial; University of Wisconsin--River Falls English Department; University of Wisconsin--River Falls Art Department; Writing; Artwork